Faktor-Faktor yang Memengaruhi Minat Belanja Mahasiswa Kota Mataram pada Live Produk di Tiktok dan Shopee - Syifa Salsabila Satya Graha; Nisa Ul Istiqomah; Ika Wulandari; Ismi Asmawati; Zulhan Widya Baskara; Dina Eka Putri; Zulhan Widya Baskara (Universitas Mataram, 2025)
The development of live shopping on the Shopee and TikTok platforms has changed consumer shopping behavior, including students in Mataram City. This study has two main objectives. The first objective is to identify eight independent variables that influence college students' shopping interest when Live shopping on the two platforms, which are analyzed using multiple linear regression. The second objective was to examine the relationship between shopping decisions and shopping interest using correlation analysis, which focused specifically on these two variables due to their significant relationship in the context of consumer action. Data was collected through a questionnaire that was tested for validity and reliability, with a Cronbach's Alpha value of 0.95 which indicates a high level of consistency. The results of the classical assumption test show that the model meets the assumption of multicollinearity, but does not meet the assumptions of normality and homogeneity. Multiple linear regression shows an R value of 0.75, which indicates a strong relationship between the independent variables and the shopping interest of respondents. Substantial factors that influence shopping interest include interaction and engagement, product quality and variety, and shopping satisfaction when Live. Meanwhile, price, influencer participation, time constraints, gender, and platform did not show a substantial influence.